Adsorptive removal of pharmaceuticals from water by commercial and waste-based carbons - Calisto, Vânia
This work describes the single adsorption of seven pharmaceuticals (carbamazepine, oxazepam, sulfamethoxazole, piroxicam, cetirizine, venlafaxine and paroxetine) from water onto a commercially available activated carbon and a non-activated carbon produced by pyrolysis of primary paper mill sludge. Kinetics and equilibrium adsorption studies were performed using a batch experimental approach. For all pharmaceuticals, both carbons presented fast kinetics (equilibrium times varying from less than 5 min to 120 min), mainly described by a pseudo-second order model. Equilibrium data were appropriately described by the Langmuir and Freundlich isotherm models, the last one giving slightly higher correlation coefficients. The fitted parameters obtained for both models were quite different for the seven pharmaceuticals under study. In order to evaluate the influence of water solubility, log Kow, pKa, polar surface area and number of hydrogen bond acceptors of pharmaceuticals on the adsorption parameters, multiple linear regression analysis was performed. The variability is mainly due to log Kow followed by water solubility, in the case of the waste-based carbon, and due to water solubility in the case of the commercial activated carbon.